The program of enteral correction of homeostasis disorders and its effect on intestinal permeability in acute poisoning - M. M. Potskhveriya; V. A. Matkevich; Yu. S. Goldfarb; A. Yu. Simonova; N. E. Stolbova; I. A. Tyurin; S. S. Petrikov (Трансплантология (Москва), 2022)
Background. The problem of pathologically increased permeability of the intestinal wall is actualized with the accumulation of information about the correlation of this phenomenon with complications of an inflammatory nature and multiple organ failure in critical conditions, including acute poisoning.Aim of study. To assess the effect of the program of enteral correction of homeostasis disorders on intestinal permeability in acute poisoning.Material and methods. 40 patients (67.5% of women and 32.5% of men) admitted at the Intensive Care Unit as part of the Scientific Department of Acute Poisonings and Somatopsychiatric Disorders of the N.V. Sklifosovsky Research Institute for Emergency Medicine were examined, 20 of them (group I) with severe acute oral poisoning with corrosive substances: acetic acid 35.6% and alkali (sodium hydroxide) 64.4 %, as well as 20 patients (group II) with severe acute oral poisoning with psychopharmacological agents. Both groups were divided into two subgroups: I-a and II-a – (10 patients in each), in whom an enteral correction program was used in addition to the standard treatment, and I-b and II-b comparison groups (10 patients in each each) who received only standard therapy.Results. It was found that in all observed patients with severe acute oral poisoning with corrosive substances, as well as psychopharmacological agents, the ratio of lactulose / mannitol concentration in urine as an indicator of intestinal permeability was increased before the start of treatment in relation to its reference value of 3.8-4.9 times.After 5 days, in patients who received the enteral correction program, the lactulose/mannitol ratio decreased by 15.4% in cases of poisoning with corrosive substances, and by 19.8% in cases of poisoning with psychopharmacological agents. At the same time, in patients with poisoning with corrosive substances, who received standard treatment, this parameter decreased by only 1%. Attention was drawn to the fact that in patients with psychopharmacological agents poisoning who received standard therapy, the intestinal permeability index after 5 days did not decrease, but continued to increase and exceeded the initial value by 11.4%.Conclusion. With the help of the enteral correction program, it is possible to reduce the permeability of the intestinal wall in acute poisoning with corrosive substances and psychopharmacological agents.